The Dynamic Impacts of Oil Price on China’s Natural Gas Consumption under the Change of Global Oil Market Patterns: An Analysis from the Perspective of Total Consumption and Structure - Jian Chai; Ying Jin (Energies, 2020)
In recent years, China’s energy structure has been adjusted unceasingly, where the proportion of natural gas has been increasing year by year, and its external dependence has also been increasing. Therefore, it is necessary to discuss the correlation between China’s natural gas market and the international energy market. This paper studies the dynamic relationship between China’s total natural gas consumption, consumption structure, and the international price of oil from the perspectives of mutation and time-variance, using the cointegration test with regime shifts and a state space model. The results show that during the global financial crisis in 2008, the cointegration relationship between China’s total natural gas consumption and the international oil price has undergone structural changes. January 2012 and March 2015 are potential structural mutation points. After the structural mutation, the impact of the international price of oil on China’s total natural gas consumption has weakened. From a structural point of view, urban gas and power generation gas have both been greatly affected by the change of oil price, while industrial gas and chemical gas are less affected. The conclusion here will provide an important empirical reference for optimizing the structure of natural gas consumption and maintaining energy security in China.